DETERMINATION OF TOTAL FLAVONOID IN JAMU “X” WITH UV-VISIBLE SPECTROPHOTOMETRIC METHODS - Perdana Priya Haresmita; Missya Putri Kurnia Pradani (Jurnal Farmasi Sains dan Praktis, 2022)
Jamu is still the choice of Indonesian people as an alternative to modern medicine until now. As a cultural heritage of the Indonesian, jamu is still very popular from the west to the east of Indonesia. The enthusiasm of the Indonesian in consuming jamu has encouraged many traditional medicine industries to produce jamu with many kinds of claim. Jamu "X" is claimed to help maintain body health. This research was conducted to determine the total flavonoid content in jamu "X" calculated as rutin by UV-spectrophotometric method with aluminum chloride (AlCl3) reagent. Jamu "X" is a product with new formula that is expected to be marketed soon. The determination of the maximum absorbance wavelength of rutin was carried out at a wavelength of 400-800 nm and the resulting maximum absorbance wavelength of rutin was 416.5 nm. The determination of total flavonoid calculated as rutin determined using a linear regression equation from the rutin standard. The linear regression equation was determined from a rutin standard curve series with 10; 12.5; 15; 17.5 and 20 g/ml, respectively and the linear regression equation obtained y = 0.0275x + 0.093. The results of the determination of rutin in the jamu "X" were 1.474%; 1.474% and 1.469% with an average value of 1.472%.